Normative Approach to Workers’ Mental Well-Being in the Digital Era - Sanja Stojković Zlatanović; Marta Sjeničić (Review of European and Comparative Law)
The paper aims to provide theoretical insights and explore the comparative legal practice of approaching mental health and well-being at the workplace by applying legal normative and comparative methods in a digitalized world of work. In this regard, subordination vs autonomy needs to be considered as a starting theoretical point accompanied by an overview of comparative legal approaches that have recently introduced some novel legal mechanisms, such as the right to disconnect to deal better with the exercise of fundamental labor rights. Additionally, introducing a psychosocial risk management model in occupational health and safety could significantly improve workers’ mental health and well-being in the digital age. Therefore, the proactive, holistic, and integrated approach to workers’ rights and status in the digital environment must be analyzed by exploring the bounding point between organizational management views on the subject and labor law standpoints.